PARTICIPATION OF THE FACULTY OF HISTORY OF THE NATIONAL UNIVERSITY OF UZBEKISTAN IN INTERNATIONAL SCIENTIFIC PROJECTS (ON THE EXAMPLE OF TACIS-TEMPUS) - Эргашев Ҳ. Ю. (TARIXIY TADQIQOTLAR, 2026)
This article is devoted to the participation of the Faculty of history of the National University of Uzbekistan named after Mirzo Ulugbek in international scientific projects and its significance, revealing its place in the scientific work of the following years and analyzing the accumulated experiences of scientific projects to continue the scope of scientific cooperation relations in the following years.